Junior and university tennis injuries: Bibliographic review and practical proposal for prevention (Agora for Physical Education and Sport, 2020)
The aim of this paper is the analysis of the existing literature related to the most common injuries in junior and university tennis in order to detect the most frequent. Furthermore, in response to the emergence of new pathologies arising from the evolution of the game of tennis characterized by increased strength and speed of play, a practical proposal for prevention is made.
Keywords: tennis; junior tennis; sport injuries; injury prevention